The Role of Corporate Social Responsibility between HR Compliances and Employee Pro-organizational Behavior - Rahaman, Md. Atikur; Imam, Hasina; Tewary, Prianka; Ashraf, Aysha; Sani, Md Shabab Ashfaque; Ali, Mohammed Julfikar; Fenyves, Veronika; Oláh, Judit (Journal of Posthumanism, 2025)
T This study indicates that the association between human resource (HR) compliances and employee pro-organizational behavior (EPB) has been comparatively less researched in academia. This empirical paper lines up with the correlation between HR compliance and EPB, considering the mediating effect of corporate social responsibility (CSR). The independent factor, HR compliance, was further divided into four components: “work environment”, “health and safety”, “flexibility of work,” ‘compensation’. For organizations wishing to increase their workforce’s pro-organizational behavior, the study offers useful insights. Partial least square structural equation modeling is employed in this research to assess the perceptions of front-line banking industry workers in Bangladesh. The findings underscore that effective management of compensation, health and safety measures, and a positive work environment significantly enhance CSR practices, which in turn positively impact EPB. While work flexibility shows some influence on CSR, its direct impact on EPB is negligible. We expect the outcomes to be contributory to the upcoming research in investigating the role of HR compliance in creating positive output from employee EPB through the sense of CSR in the industry sector. Further, such a research effort can aid the organization’s policymakers motivate employees for their positive pro-organizational behavior.